EVALUASI PELAKSANAAN PERENCANAAN PULANG - Liliana Dewi Purnamasari; Chandra Bagus Ropyanto (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Discharge planning is a behavior of nurses in nursing services. Common implementation of discharge planning is only given when the patient will go home from the hospital. A descriptive research about discharge planning showed that nurses who did discharge planning when the patient go home from the hospital were 89, 47 % (Setyowati, 2011).The purpose of this research was to identifying the implementation of discharge planning. The research was a descriptive research with cross sectional design. The respondents are 103 taken by purposive sampling technique. The results of the research indicated that 48 (46.6%) respondents are well enough in implementation of discharge planning. The advice for nurses departement in the hospital to arrange the standard of discharge planning in a short time.